Dampak Pandemi Covid-19 terhadap Pembiayaan Pendidikan Siswa MTS. PAB 5 Helvetia - M. Ikbal; Sri Leny; Syaiful Anwar Lubis; Aan Andrianto (AUD Cendekia, 2022)
The purpose of this study was to obtain information on the impact of education financing on PAB 5 Helvetia tsanawiyah students. Where in accordance with government policy during the Covid-19 pandemic, the implementation of learning which is usually carried out face-to-face is abolished and transferred to online learning. In accordance with government regulations related to severing the spread of the Covid-19 chain. This is so that the learning process will continue to be carried out without stopping in accordance with the mandate of the 1945 Constitution, but based on research conducted during the Covid-19 study, an online learning model was carried out through the use of the Zoom application, Google Classroom and WhatsApp group. The impact of the pandemic on student funding is very much felt because they have to fulfill technological devices and internet quotas in online learning, while the economic situation is not supportive of meeting these learning needs.